Ethno-cultural aspects of artistic and musical education and its axiological foundations - Yusupova A. A, Esdauletova K. A, Elzhanov D. N, Sydykova R. Sh, Narbekova B. M, Kakimova L. Sh, Tobagabylova A. Zh. (Opción, 2020)
The process of globalization in the new millennium accentuates various areas of human activity, formation of new integrated cultural space, traditional culture and continuity of traditions in the process of preservation of spiritual heritage of people. The aim of this paper is to examine prerequisites and conditions for the spiritual development of the community that is able to understand the value of cultural diversity. Results show that the potential of the spiritual-traditional and innovative refraction through the lens of musical and anthropological knowledge facilitates the perception of centuries-old human value-based achievements.